Coparenting Model to Preventing the Incidence of Postpartum Blues And Increasing the Success of Exclusive Breastfeeding - Gusti Ayu, Martha Winingsih (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Breastfeeding difficulties can increase the risk of postpartum blues and hinder exclusive breastfeeding success. Husband and family support are key factors in reducing postpartum blues. This study aimed to identify determinants of exclusive breastfeeding and evaluate the effect of a Balinese culture-based coparenting model in preventing postpartum blues to improve breastfeeding success. A mixed methods approach with an explanatory sequential design was used, involving 11 informants (7 married couples and 4 experts) and 60 respondents divided into intervention and control groups. The intervention applied the Balinese coparenting model